High-Entropy Alloys as an Alternative Binder to Improve Mechanical, Tribological, and Oxidation Properties of Cermets - Jimenez-Arevalo, V; Jimenez-Arevalo, V (Elsevier Ltd, 2024)
Due to elevated potential associated with the extremely vast compositional space of high-entropy alloys (HEAs), there is a significant drive to explore these alloys in high-performance contexts such as intensive wear and oxidative environments. In this regard, this review article comprehensively explores the utilization of HEAs in cemented carbides, focusing on their role as binders in cermets. The wear resistance and oxidation behavior of HEA-containing cermets depends on the ceramic-binder thermodynamic compatibility, phase transformations during sintering, microstructure, and mechanical properties. Hence, much high quality research has been focused into exploring the combination of several HEAs with tungsten carbide, titanium carbides, nitrides, carbonitrides and diborides along with other ceramic compounds. As there are many HEA-ceramic combinations, this review aims to provide a landscape of the developments in this field, providing detailed information about the chemical compositions, sintering techniques, mechanical properties and wear and oxidation resistance obtained. Finally, the need for further research to fully understand the complex interactions between composition, microstructure, and wear and oxidation resistance is highlighted, aiming to tailor HEA compositions for optimized performance. The findings presented in this review contribute valuable insights into the promising applications of HEAs in cemented carbides. © 2024 The Authors